COGNITIVE DIVERSITY AMONG EFL LEARNERS: IMPLICATIONS FOR TEACHING IN HIGHER EDUCATION - Elyas, Tariq; AlHashmi, Bayan; Fang, Fan (TEFLIN Journal, 2020)
With a theory-driven interest in the factors that make some language learners more successful than others, this study attempts to measure the cognitive diversity level of EFL learners at a Saudi university. To achieve this purpose, the Ehrman and Leaver’s questionnaire of learners’ cognitive profiles (Ehrman & Leaver, 2003) was adapted, translated into Arabic, and then randomly distributed to foundation year students taking English as a Foreign Language as a main course. The overall results reveal that the cognitive diversity among students is considerable. It ranges between moderate to high, according to the Simpson Diversity Index (Simpson, 1949). On this account, several implications are suggested to improve the quality of EFL teaching at the university level. These implications and recommendations are mostly directed to the committees concerned with qualification assurance or professional development.